Explaining low rates of sustained use of siphon water filter: evidence from follow-up of a randomised controlled trial in Bangladesh - Najnin, Nusrat; Arman, Shaila; Abedin, Jaynal; Unicomb, Leanne; Levine, David; Mahmud, Minhaj; Leder, Karin; Yeasmin, Farzana; E. Luoto, Jill; Albert, Jeff; P. Luby, Stephen (© 2015 Blackwell Publishing Ltd., 2017)
This article was published in Tropical Medicine and International Health [© 2015 Blackwell Publishing Ltd.] and the definite version is available at: http://www.pubpdf.com/pub/25495859/Explaining-low-rates-of-sustained-use-of-siphon-water-filter-evidence-from-follow-up-of-a-randomised